Online Mediation in The Malaysian Shariah Court: Its Benefits and Challenges (International Seminar on Syariah and Law (INSLA), 2020)
Achieving amicable settlement of disputes has been promoted in various Islamic legal texts. Mediation or sulh at the Malaysian Shariah Court is a branch of alternative dispute settlement established since 2001. Sulh aims to cease on-going hostilities between the parties and restore their relationship peacefully. The outbreak of Covid-19 pandemic gives an impact on the marriage system among the Malaysian Muslim community as it is reported that there is a total of 6,569 couples divorced from March 18 to June 18, 2020. With the new norm, there is an innovative initiative introduced by the Selangor Shariah Judiciary Department (JAKESS). The Department has recently implemented online mediation or online sulh. This online sulh is executed using a video conference facility developed by the Malaysian Administrative Modernisation and Management Planning Unit (MAMPU). In empowering the court operation during the movement control order (MCO) and post MCO, JAKESS has introduced its “Operation Guidelines” which covers guidelines on online sulh too. The guidelines are in two volumes, namely the courts’ operation within the MCO period starting May 13, 2020, and post MCO period begins on Jun 10, 2020. This guideline aims to guide the sulh officers, parties, lawyers and court officials in conducting sulh session for parties who had their settlements on the disputes and those who are yet to have an amicable settlement but wish to undergo online sulh within this period. A pilot case involving online sulh case at the Shariah High Court has been successfully conducted on 21stMay 2020 to test on the effectiveness of the SOP that has been developed. The paper adopts library-based and qualitative research methodologies including the interview. This paper aims to discuss the advantages and disadvantages of online sulh, the issues and challenges faced in administering the conduct of online sulh in Malaysia. The existing operation standard introduced by JAKESS will be examined and experienced by the sulh officers conducting online sulh will also be discussed. Lastly, the paper will recommend the way forward for optimal use of online video conferencing into sulh practice.